2007
DOI: 10.1002/bjs.5690
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide predicts cardiac morbidity and mortality after major surgery

Abstract: Preoperative serum BNP concentration predicted postoperative cardiac events in patients undergoing major non-cardiac surgery independently of other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 33 publications
2
46
0
1
Order By: Relevance
“…Patients with OSA had significantly lower levels of CPK when compared with non-OSA patients [137] Won et al increase in the hazard of death and 6.9-fold increase in hazard of cardiovascular mortality [24] Gibson et al of risk factors and after adjusting for: sex, ischemic heart disease, heart failure, cerebrovascular disease, renal impairment, type of surgery, use of beta-blockers and statins [40] Dernellis et al Sleep apnea in TJA patients & the role for cardiac biomarkers for risk stratification Review sequently contributed to the release of cTns [60]. Additionally, the authors state, the use of a high-sensitive assay could have been more useful in detecting the smaller sized cTnI molecule [60].…”
Section: Troponins As a Marker Of Cardiovascular Risk In Tjamentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with OSA had significantly lower levels of CPK when compared with non-OSA patients [137] Won et al increase in the hazard of death and 6.9-fold increase in hazard of cardiovascular mortality [24] Gibson et al of risk factors and after adjusting for: sex, ischemic heart disease, heart failure, cerebrovascular disease, renal impairment, type of surgery, use of beta-blockers and statins [40] Dernellis et al Sleep apnea in TJA patients & the role for cardiac biomarkers for risk stratification Review sequently contributed to the release of cTns [60]. Additionally, the authors state, the use of a high-sensitive assay could have been more useful in detecting the smaller sized cTnI molecule [60].…”
Section: Troponins As a Marker Of Cardiovascular Risk In Tjamentioning
confidence: 99%
“…Studies measuring BNPs in patients undergoing noncardiac surgery have investigated the role in the perioperative period for risk prediction or associations with adverse postoperative myocardial events [35][36][37][38][39][40][41][42][43][44], prolonged hospital stay [45] and mortality [24,[46][47] (see Table 4). Most of the studies evaluating BNPs had levels drawn within 2 weeks prior to the day of surgery, typically at one time-point, however recent studies have incorporated perioperative BNP levels (levels drawn preoperatively and up to 5 days following surgery) [36,38,43,[45][46].…”
Section: Brain Natriuretic Peptides As a Marker Of Cardiovascular Rismentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining studies, three reported exclusively on patients undergoing emergency surgery, 38,45,48 and one documented both elective and emergency surgeries that were classified as being high risk. 46 Certain studies investigated outcomes in a specific surgical discipline, including thoracic surgery (4), 36,50,51,54 vascular (7), 29,40,42,44,55,57,59 orthopaedic (5), 45,[47][48][49]60 major abdominal (1), 56 oesophagectomy (1), 41 while the rest documented outcomes following a variety of surgeries performed (10), 34,35,[37][38][39]43,46,52,53,58 including a mix of general, head and neck, gynaecological, orthopaedic, vascular, urological, neurosurgery and thoracic surgery.…”
Section: Included Studiesmentioning
confidence: 99%
“…All of the included studies demonstrated that an elevated preoperative NP measurement was an independent predictor of the primary study outcome. 39 was a prospective derivation study with a subsequent validation study performed; one 44 was a prospective prespecified secondary analysis of a cohort in a placebo-controlled randomised controlled trial (RCT); one 45 was a cohort extracted from a prospective observational study; and one 54 was a retrospective review of patients enrolled in a different study with prospectively collected data.…”
Section: Association Between Nps and Postoperative Major Adverse Cardmentioning
confidence: 99%